Effect of nitrogen, phosphorus and potassium availability on emergence, nodulation and growth of Trifolium medium L. in alkaline soil - Chmelíková, L; Hejcman, M (Plant biology (Stuttgart, Germany), 2014)
Little is known about the effects of nutrient availability on the growth of Trifolium medium in alkaline soil. In 2010, a pot experiment (10 N, P and K fertiliser treatments) with seeding of T. medium into alkaline soil was performed and emergence of seedlings, survival, aboveground and belowground organs were studied. The positive effects of increased nutrient availability on seedling emergence ranged from 5% in the control to 17% in the high P treatment. The lowest mortality was in treatments with P and K supply and the highest in treatments with N supply, due to the sensitivity of young plants to high N availability. The highest values of most measured aboveground plant traits were recorded in treatments with simultaneous application of N, P and K. There were highly positive effects of P supply alone or in combination with N and K on the development of belowground organs. Taproot length ranged from 11.5 in high N to 40.2 cm in P treatment. There was a negative effect of N application on nodulation, especially in N treatments, where growth of T. medium was limited by insufficient P supply. The number of nodules per plant ranged from 0.8 to 4.5 in the high N and P treatments. As demonstrated in this study, T. medium is a potentially suitable legume for alkaline soils. It requires a relatively high P and K supply as well as moderate mineral N supply to achieve its maximum growth potential.
Keywords: draslík; Flowers; zigzag clover; Trifolium; semenáček; Plant Roots; Phosphorus; kořeny rostlin; Seedlings; Nitrogen; Flowering; Potassium; dusík; mineral nutrition; phenotypic plasticity; květy; fosfor; roots